INSTITUTIONAL APPROACHES OF MODERN SOCIO-ECOLOGO-ECONOMIC FORMS OF ECONOMY IN AGRARIAN SECTOR OF ECONOMY OF UKRAINE - O. Pimenova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Main problems of agrarian sector of economy of Ukraine are revealed. Main directions of development of agriculture of Ukraine are determined. The necessity of socio-ecologo-economic agrarian sector is proved. Tendencies of institutionalization of forms of economy in a system of agrarian relationship were investigated. The necessity of creation of effective system of institutions with an aim of functioning effective and rational forms of economy in agrarian sector of Ukraine, which could provide a balancing of economic, social and ecologic spheres, is confirmed. In the paper is proved the necessity of creation and function of social-ecologo-economic model of agriculture development, where a social-ecologo-economic development is characterized like economic development of rural territories, rural employment in agriculture, the efficiency of employment, ecologo-safe production focused on human needs and etc., on the one side and on the other side is a significant role of rural social capital. Based on the analysis of scientific literature, it's confirmed that development socio-ecologo-economical forms of economy are accompanied with modification of the institutional structure of regulation of agriculture. It's proved that the functioning of effective forms of economy promotes the competitiveness of the agricultural sector of the national economy.